2001
DOI: 10.4049/jimmunol.167.8.4566
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CD8 T Cell Functions Mediate Susceptibility to Histoplasmosis During Chronic Viral Infection

Abstract: It has long been recognized that some viral infections result in generalized immune suppression. In acute infections, this period of suppressed immunity is relatively short. However, chronic infections associated with a prolonged period of immune suppression present far greater risks. Here, we examined the role of CD8 T cell responses following viral infection in immunity to systemic histoplasmosis. Although wild-type mice with systemic histoplasmosis were able to control the infection, those simultaneously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Given the myriad roles of type I IFNs in the host, the possible effects of induction of IFN-␤ cells infected with H. capsulatum could include modulation of (i) downstream cytokine production, (ii) apoptosis of infected macrophages, or (iii) specific aspects of the adaptive immune response to H. capsulatum. Interestingly, it was previously observed that chronic infection of macrophages or mice with lymphocytic choriomeningitis virus (LCMV) clone 13, which induces type I IFNs, caused sensitization of the host to H. capsulatum infection (84,90). Although the possible interpretations of these data are complex, they are consistent with the model that increased levels of type I IFNs correlate with increased sensitivity to H. capsulatum infection.…”
Section: Vol 78 2010supporting
confidence: 76%
“…Given the myriad roles of type I IFNs in the host, the possible effects of induction of IFN-␤ cells infected with H. capsulatum could include modulation of (i) downstream cytokine production, (ii) apoptosis of infected macrophages, or (iii) specific aspects of the adaptive immune response to H. capsulatum. Interestingly, it was previously observed that chronic infection of macrophages or mice with lymphocytic choriomeningitis virus (LCMV) clone 13, which induces type I IFNs, caused sensitization of the host to H. capsulatum infection (84,90). Although the possible interpretations of these data are complex, they are consistent with the model that increased levels of type I IFNs correlate with increased sensitivity to H. capsulatum infection.…”
Section: Vol 78 2010supporting
confidence: 76%
“…Because PD-1 was shown to be upregulated on exhausted CD8 ϩ T cells in chronic viral infections such HIV, it is reasonable to suggest that blockade of the PD-1 pathway would benefit the host immune response against both pathogens through restoration of the antiviral function of CD8 ϩ T cells and abolishing T cell suppression mediated through Hc-infected antigen-presenting cells (APCs). This supposition is supported by the finding that sublethal Hc infection associated with persistent infection of LCMV clone 13 resulted in reduced immunity leading to increased fungal burdens and high mortality (33). Because LCMV has been shown to cause exhaustion of CD8 ϩ T cells through up-regulation of PD-1 (14), it is intriguing to consider that Hc can cause fatal disease in these mice by efficiently avoiding host immune responses in the setting of high expression of both PD-Ls and PD-1.…”
Section: Discussionmentioning
confidence: 81%
“…They might provide B cell help or serve an immunoregulatory role through secretion of cytokines; these activities would be limited to conditions of high peptide/class I MHC density, for example when the APC is infected with an intracellular pathogen or when Ag loads are high due to persistent infection. Alternatively, they might represent a feedback response to intense or prolonged IL-4 exposure whereby down-regulation of CD8 reduces sensitivity to Ag, dampening the effector response and reducing the immunopathology associated with prolonged T cell activation and function (46,47). Either outcome might be exploited by tumors or infectious agents to escape elimination by cytolytic CD8 high T cells.…”
Section: Discussionmentioning
confidence: 99%